Effects of NaCl and seawater induced salinity on survival and reproduction of three soil invertebrate species. (September 2015) - Pereira, C.S.; Lopes, I.; Sousa, J.P.; Chelinho, S.
Highlights: The effects of salinisation on soil ecosystems due to sea level rise were assessed. Soil invertebrates were exposed to NaCl and seawater in OECD soil. Increased sensitivity observed: H. aculeifer  ≪  E. crypticus  ≈  F. candida . Soil invertebrate sensitivity to NaCl depends from the exposure pathway. Adverse effects were found for soil conductivity values below the limit defined for saline soils. Abstract: The increase of global mean temperature is raising serious concerns worldwide due to its potential negative effects such as droughts and melting of glaciers and ice caps leading to sea level rise. Expected impacts on soil compartment include floodings, seawater intrusions and use of saltwater for irrigation, with unknown effects on soil ecosystems and their inhabitants. The present study aimed at evaluating the effects of salinisation on soil ecosystems due to sea level rise. The reproduction and mortality of three standard soil invertebrate species ( Folsomia candida, Enchytraeus crypticus, Hypoaspis aculeifer ) in standard artificial OECD soil spiked with serial dilutions of seawater/gradient of NaCl were evaluated according to standard guidelines. An increased sensitivity was observed in the following order: H. aculeifer  ≪  E. crypticus  ≈  F. candida consistent with the different exposure pathways: springtails and enchytraeids are exposed by ingestion and contact while mites are mainly exposed by ingestion due to a continuous and thick exoskeleton. Although small differences were observed in the calculated effect electrical conductivity values, seawater and NaCl induced the same overall effects (with a difference in the enchytraeid tests where a higher sensitivity was found in relation to NaCl). The adverse effects described in the present study are observed on soils not considered saline. Therefore, the actual limit to define saline soils (4000 μS cm −1 ) does not reflect the existing knowledge when considering soil fauna.